Microbial protein extraction from palm oil mill effluent - Nor Faizah J. (2024)
Palm oil mill effluent (POME) is abundantly produced during palm oil milling process and is treated for pollutant reduction without any revenue or profit. The main objective of this research was to evaluate POME as a substrate for microbial protein production and analyse the removal rate of pollutant. This study used hydrolysed POME containing fermentable sugars as carbon source for the cultivation of microbes. Raw POME was initially pre-treated with Celluclast® enzyme using the following conditions: Concentration (1.5% to 5.0% v/v); incubation temperature (45℃-55℃), rotation speed (100-200 rpm) and pH (4.0-5.5). After pre-treatment, the hydrolysate contained 41.63 g L–¹ reducing sugars with 56 000 mg L–¹ chemical oxygen demand (COD). Baker’s Yeast (Saccharomyces cerevisiae) was then cultivated onto the raw or hydrolysed POME at 30℃ for seven days. The amount of yeast biomass produced was 28.92 g L–¹ with 24.79% protein content. Adding to this, the COD value was reduced by 79.12%. The yeast fermentation in hydrolysed POME recorded the highest increase in biomass and protein contents of 3.44 and 7.74 folds, respectively. The findings revealed that POME is a promising raw material for microbial biomass protein production and simultaneously remove the pollutant from POME.